Development and Characterization of Clioquinol Nanocrystals - Lima dos Santos, Francielli; Capp Zilles, Julia; Jacobus Berlitz, Simone; Clemes Kulkamp Guerreiro, Irene; Meneghello Fuentefria, Alexandre; Vidor Contri, Renata (Drug Analytical Research, 2026)
Drug nanocrystals, composed solely of active substance and stabilizer, have recently been proposed for cutaneous applications, including the management of skin fungal infections (dermatomycoses), which are often difficult to treat. Clioquinol nanocrystals were obtained using different preparation methods, drug concentrations, surfactants, and bead sizes. The selected nanocrystal suspension (bead milling, 1% drug, 1% polysorbate 80) exhibited an average particle size of approximately 300 nm (polydispersity index of 0.254), a zeta potential of −7.6 mV, a pH value of 5.4, a drug content of about 97% (relative to 10 mg/mL), and a nanocrystallization efficiency of approximately 96%. The presence of the surfactant was essential to ensure nanocrystal stability for 90 days at room temperature. Overall, the results indicate that clioquinol nanocrystals are possible to be obtained by small-scale wet bead milling and present suitable nanometric features, being considered a promising alternative as cutaneous antifungal therapy.